Modelling of a fixed bed reactor for Fischer–Tropsch synthesis of simulated N2-rich syngas over Co/SiO2: Hydrocarbon production. (15th August 2015) - Moazami, Nima; Wyszynski, Miroslaw L.; Mahmoudi, Hamid; Tsolakis, Athanasios; Zou, Zhi; Panahifar, Pooria; Rahbar, Kiyarash
Highlights: Pseudo-homogeneous mathematical modelling of fixed bed reactor for FT synthesis. Prediction of conversion rate and products' selectivity for the designed FT plant on cobalt-silica catalyst. Calculation of kinetic parameters for the proposed model using experimental data. Numerical investigation on effects of operating conditions on conversion and selectivity. Abstract: A numerical pseudo-homogeneous one-dimensional mathematical model of a mini-scale laboratory fixed bed reactor for Fischer–Tropsch (FT) synthesis was developed. FT synthesis was modelled for simulated N2 -rich syngas (17%Vol CO, 33%Vol H2, and 50%Vol N2 ) on a cobalt-silica (i.e. Co/SiO2 ) catalyst/support. The performance of the reactor model for gas/liquid fuel production was studied at different operating conditions i.e. temperature of 503–543 K, pressure of 10–25 bar and gas hourly space velocity (GHSV) of 1800–3600 Nml gcat −1 h −1 . An algorithm was written in order to calculate the conservation of species, pressure drop, reaction rate equations and physicochemical and thermodynamic properties' relationships along the axial dimension i.e. in the flow direction. The program code was executed in a MATLAB environment to describe the profiles of concentration of each individual component in the gas phase along the reactor. The model was capable of predicting the selectivity of different product species and conversion of CO and H2 in the flow direction. The power law rate expression was chosen for the rate of reaction and the dominating FT and Water Gas Shift (WGS) reaction equations were considered in accordance with the literature. After the mechanisms and rate equations were derived, the kinetic data (e.g. rate constant ( kj ), for reaction 'j' ) for the proposed reaction equations were obtained as "integral reactor data" where the total conversion is measured as a function of: catalyst weight to flow rate ratio (i.e. W/F), inlet pressure, final conversion obtained by experiment, and inlet fluid temperature. The pre-exponential factors ( Aj ) were calculated by the classic Arrhenius equation using the predicted kj and literature-derived activation energies ( Ej ). Finally, the partial order of reactions with regard to CO ( mj ) and H2 ( nj ) were calculated for the power law rate equation using MATLAB Global Optimization Toolbox with additional in-house procedures according to the results acquired from experiments with the Co/SiO2 catalyst. The predicted results of the model were validated successfully against 16 experimental conditions with respect to conversion of CO and selectivity of products species such as CO2, CH4, C2, C3, C4, and C5+ . The error between the predicted and experimental results was negligible. Finally, the influence of the GHSV, temperature and inlet pressure of fluid mixture on components' selectivity and conversion, were also investigated and the conclusions were in agreement with the literature.